Primary Progressive Multiple Sclerosis Under Anti-TNFα Treatment: A Case Report. (December 2020) - Iovino, Aniello; Aruta, Francesco; Dubbioso, Raffaele; Ruggiero, Lucia; Tozza, Stefano; Spina, Emanuele; Manganelli, Fiore; Iodice, Rosa
Antagonists of tumour necrosis factor α (TNFα) are a common therapeutic choice for autoimmune diseases. Although they are effective and relatively safe, an increasing number of immune-mediated adverse events have been reported. Among these, neurological adverse effectsm such as consisting of demyelinating events in the central and peripheral nervous system were described. Demyelination of the central nervous system is a rare complication after treatment with TNFα antagonists. Here, we report a case of multiple sclerosis under treatment with TNFα antagonists and discuss its etiopathogenesis. This 45-year-old female patient developed signs and symptoms suggestive of primary progressive multiple sclerosis during treatment with adalinumab for nodular cystic acne, and magnetic resonance imaging of the patient showed typical lesions of demyelinating disease.